Economic Empowerment of Community Groups of Sei Beliung Urban Village Through Organic Vegetable Plant Cultivation with Hydroponics System - Okto Ivansyah; Iwan Rusiyardi; Ichsan Ichsan; Jaini Fakhruddin (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
Sei Beliung is one of the urban villages in Pontianak city, with 80% of high school graduates and main livelihood is 60% of workers. Men work as laborers, while their mothers help their husbands to support their family's economy. Based on field data most of the homes in Sungai Beliung have large yard. To optimize the efforts of mothers to help their husbands in supporting the economy, the Community Service (PPM) activity aims to empower the community's economy by fostering mothers using the yard through organic vegetable cultivation of hydroponics system. This activity has the main objective is to provide farming skills with hydroponic system for the community of RT 02 and RT 04 of Sui Beliung Subdistrict so that it can produce organic vegetables to be utilized as their life support.